2022
DOI: 10.1101/2022.11.01.22281803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preventable deaths involving medicines in England and Wales, 2013-22: a systematic case series of coroners’ reports

Abstract: Objectives: To identify medicines-related deaths in coroners reports and to explore concerns to prevent future deaths. Design: Retrospective case series of coroners Prevention of Future Deaths reports (PFDs). Setting: England and Wales. Participants: Individuals identified in 3837 PFDs dated between 1 July 2013 and 22 February 2022, collected from the UK Courts and Tribunals Judiciary website using web scraping, and populated into an openly available database: https://preventabledeathstracker.net/ Main outcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For example, in our own recent survey of 3785 reports from coroners, the coroners received responses to only 49% of the medicines-related reports, 12 despite the fact that by law responses must be received within 56 days.…”
Section: Efficacymentioning
confidence: 95%
“…For example, in our own recent survey of 3785 reports from coroners, the coroners received responses to only 49% of the medicines-related reports, 12 despite the fact that by law responses must be received within 56 days.…”
Section: Efficacymentioning
confidence: 95%
“…Since 2013, 19% of 3785 PFDs have reported deaths associated with medicines, with opioids (22%), antidepressants (9.7%), and hypnotics (9.2%) being most commonly involved 1. Concerns that coroners expressed often related to patient safety (29%) and communication (26%), including failures of monitoring (10%) and poor communication between organisations (7.5%).…”
Section: Frequency Of Medicines-related Pfdsmentioning
confidence: 99%
“…Individuals or organisations that receive a PFD are statutorily required to respond to the coroner within 56 days of receiving the report, outlining actions proposed or already taken to tackle the concerns that the coroner has expressed. Since 2013, 19% of 3785 PFDs have reported deaths associated with medicines, with opioids (22%), antidepressants (9.7%), and hypnotics (9.2%) being most commonly involved 1. Concerns that coroners expressed about these deaths often related to patient safety (29%) and communication (26%), including failures of monitoring (10%) and poor communication between organisations (7.5%).…”
mentioning
confidence: 99%
“…Several studies have investigated coroners' concerns in PFDs [9][10][11][12][13][14] , yet none has focused exclusively on opioid-related deaths, although opioids have previously been implicated as the most common medicine type causing preventable deaths 14 . These studies have similarly found poor response rates from recipients receiving PFDs 9,25 and wide geographical variation in the writing of reports 9,26 , concerns that were also highlighted in a 2021 report by the House of Commons Justice Select Committee.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A case series of medicine-related PFDs showed that opioids were the most common drug involved in deaths. 14 However, these concerns have not been synthesised. A systematic assessment of opioid-related PFDs and their associated responses might therefore provide valuable information to inform public health strategies to reduce opioid deaths.…”
Section: Introductionmentioning
confidence: 99%